Optimalisasi Layanan Kesehatan Penyandang Disabilitas Berbasis Pelatihan Disability Inclusive Development di RS Lamongan - Rudi Wibowo; Nuning Nurna Dewi (ServeInnovate: Journal of Applied Community Engagement (SJACE), 2026)
Persons with disabilities continue to experience multiple barriers in accessing quality healthcare services, including physical, communication, and systemic obstacles. These challenges highlight the need to strengthen healthcare workers’ capacity and develop more inclusive healthcare systems. This community service program aimed to enhance hospital staff’s knowledge and skills in delivering inclusive healthcare services for persons with disabilities through a Disability Inclusive Development (DID) approach. The program was conducted at a hospital in Lamongan Regency and involved 33 staff members from various service units. The implementation methods included theoretical training, focus group discussions, healthcare service simulations, and evaluation using pre-test and post-test instruments. The results showed an improvement of approximately 60–75% in participants’ understanding, particularly regarding the social model of disability, ethical and effective communication with diverse disability groups, and awareness of systemic barriers in healthcare services. Service simulations revealed that the main barriers were cultural, structural, informational, and institutional in nature, originating from healthcare systems that were not yet fully inclusive. This community service activity demonstrates that a DID-based approach contributes to strengthening human resource capacity and comprehensively identifying service barriers. The proposed training and simulation model is potentially replicable and may be adopted by other healthcare facilities to support the development of comprehensive, inclusive, and sustainable healthcare systems.